1995
DOI: 10.1055/s-2007-1006549
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Continuous Systemic Infusion of Iloprost, A Stable PGI-2 Analog, on the Survival of Experimental Skin Flaps

Abstract: Numerous investigators have attempted to enhance the survival of ischemic experimental skin flaps using various pharmacologic manipulations. Recently, the authors' laboratory demonstrated the beneficial effect of iloprost, a stable PGI2 analogue, as a post-ischemic perfusion washout, in improving the survival of ischemic skin flaps. The rat unilateral abdominal skin flap, based on the superficial epigastric vessels, was utilized in this study involving 30 animals. The animals were divided into three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…It produces smooth muscle cell relaxation and vasodilation. 58 Prostacyclin and another stable analog, carbacyclin, have been tested by other investigators in rabbit epigastric flaps and were shown to significantly improve flap survival. 56 Iloprost.…”
Section: Pharmacotherapeutics: An Effort To Improve Free Flap Survivalmentioning
confidence: 99%
“…It produces smooth muscle cell relaxation and vasodilation. 58 Prostacyclin and another stable analog, carbacyclin, have been tested by other investigators in rabbit epigastric flaps and were shown to significantly improve flap survival. 56 Iloprost.…”
Section: Pharmacotherapeutics: An Effort To Improve Free Flap Survivalmentioning
confidence: 99%
“…Initial reports in the management of acute limb ischemia following intra-arterial drug injection are also encouraging [4]. They have also been tried as an adjunct to infragenicular bypass surgery [I] and following microvascular skin-flap reconstruction [5] but their efficacy for these conditions has not been proven by randomized controlled trials.…”
Section: Clinical Usementioning
confidence: 99%
“…Οι προςταγλαδίνεσ PGE και PGI παρουςιάηουν ιςχυρι αγγειοδιαςταλτικι δράςθ, ενϊ οι προςταγλαδίνεσ PGF και θ κρομβοξάνθ αγγειοςυςταλτικι. Ρειράματα ςε επίμυεσ, κονίκλουσ και χοίρουσ με προςταγλαδίνεσ PGE 1 και PGI, ζχουν ςτακερά δείξει ότι προκαλοφν αφξθςθ ςτθ δερματικι αιματικι ροι [135][136][137][138][139][140][141] . Ραρά ταφτα, οι παράγοντεσ αυτοί ζχουν εξαιρετικά βραχφ χρόνο θμιςείασ ηωισ, είναι αςτακείσ και απαιτοφν ςυνεχι ενδοφλζβια ι ενδοαρτθριακι χοριγθςθ.…”
Section: προςταγλαδίνεσ και αναςτολείσunclassified